Management of higher education facilities in the UK and Ukraine - Tsypanova, Nataliia (My University, 2018)
Тема цієї статті – продемонструвати відмінності та спільні риси управління системою вищої освіти Великобританії та України. Об’єктом аналізу є Університет Ворвіка, що знаходиться у Великобританії, та Національний університет харчових технологій України. Метою статті є дослідити, як у Великій Британії та Україні здійснюється управління вищими навчальними закладами, та підкреслити ключові особливості обох підходів. Управління закладами вищої освіти вивчається як «внутрішнє», так і «зовнішнє», тобто як самоврядування, так і взаємодія університетів з урядом. Найбільше уваги приділяється «внутрішньому» управлінню, оскільки воно має більший вплив на повсякденну рутину навчальних закладів. The topic of this article is to demonstrate the difference and common features of management of system of higher education in the United Kingdom and Ukraine. The subject on analysis includes University of Warwick located in the UK and National University of Food Technologies, Ukraine. The aim of the article is to investigate how higher education facilities are managed in the UK and Ukraine keeping and to underline key features of both approaches. Management of higher education facilities is studied as both “inner” and “outer” i.e. both self-governance and universities’ interaction with government. Most attention is drawn to “inner” management as it has more influence on day-to-day routine of education facilities.
Keywords: державний університет; вчена рада; наглядова рада; проректор; заступник ректора; state-owned university; academic council; supervisory board; vice-chancellor; deputy to rector; кафедра ділової іноземної мови та міжнародної комунікації